2000
DOI: 10.1038/35001638
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the intact transactivation domain of the human papillomavirus E2 protein

Abstract: Papillomaviruses cause warts and proliferative lesions in skin and other epithelia. In a minority of papillomavirus types ('high risk, including human papillomaviruses 16, 18, 31, 33, 45 and 56), further transformation of the wart lesions can produce tumours. The papillomavirus E2 protein controls primary transcription and replication of the viral genome. Both activities are governed by a approximately 200 amino-acid amino-terminal module (E2NT) which is connected to a DNA-binding carboxy-terminal module by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 23 publications
4
116
0
1
Order By: Relevance
“…We therefore studied the relationship between ectopically coexpressed Adaptor-independent activation of caspase 8HPV18 E2 protein induces caspase 8 oligomerization within filaments independently of FADD through direct interaction. Analysis of the crystal structure of the aminoterminal domain of the HPV16 E2 protein did not reveal the presence of an obvious DFD typically composed of six a-helices structures, 14 indicating that E2 may not act as a typical DFD adaptor to induce caspase 8 activation. We therefore investigated whether caspase oligomerization within filaments in the presence of E2 could be mediated by the endogenous DFD adaptor FADD, which should then be found in the insoluble filaments together with E2 and caspase 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore studied the relationship between ectopically coexpressed Adaptor-independent activation of caspase 8HPV18 E2 protein induces caspase 8 oligomerization within filaments independently of FADD through direct interaction. Analysis of the crystal structure of the aminoterminal domain of the HPV16 E2 protein did not reveal the presence of an obvious DFD typically composed of six a-helices structures, 14 indicating that E2 may not act as a typical DFD adaptor to induce caspase 8 activation. We therefore investigated whether caspase oligomerization within filaments in the presence of E2 could be mediated by the endogenous DFD adaptor FADD, which should then be found in the insoluble filaments together with E2 and caspase 8.…”
Section: Resultsmentioning
confidence: 99%
“…7,25 RFP-E2 was obtained by inserting the RFP ORF (from pDSRed2) in place of the GFP ORF in the GFP-E2 expression plasmid. E2 helices H1 (aa 1-26), H2 (aa 27-53) or H3 (aa 54-88) corresponding to the three first a-helices of the amino terminal of HPV18 E2 as determined by the crystal structure, 14 were cloned by a conventional PCR-based technique in frame with GFP. The caspase 8 prodomain (aa 1-181) was cloned in pcDNA, DED A (aa 1-93) DED B (aa 94-181) were cloned in frame with GFP and caspase domain CD (aa180-480) in frame with a N-terminal FLAG tag in pcDNA 3.…”
Section: Methodsmentioning
confidence: 99%
“…Crystal structures have been reported for the TAD of HPV16 (amino acids 1-201) (20) and for a truncated TAD of HPV18 (amino acids 66 -215) lacking two N-terminal ␣-helices (21). The HPV16 and -18 TADs share ϳ45% sequence identity (see Fig.…”
mentioning
confidence: 99%
“…The results of transcription repression studies reported here support an antiparallel DNA loop in which the GalR dimer bound to O I stacks upon the one bound to O E , consistent with the previous theoretical calculations (Geanacopoulos et al 2001). The approach reported here can be generally applicable to trace DNA trajectories in DNA loop-containing multiprotein complexes based on the "modular" principle (Antson et al 2000;Dodd et al 2001).…”
mentioning
confidence: 99%